Experiencing breast cancer in the context of mental illness in New Zealand. (2nd January 2020) - Peterson, Debbie; Cunningham, Ruth
ABSTRACT: This study aimed to explore the experiences of women with mental illness who had also experienced breast cancer diagnosis and treatment, in particular, to identify barriers and facilitators to cancer treatment. Semi-structured interviews were conducted with ten breast cancer survivors who had had contact with secondary mental health services prior to their cancer diagnosis. Thematic analysis was used to identify key themes. Participants described positive experiences of cancer treatment, expressing surprise at both how well they coped with diagnosis and treatment and how well they were treated by services. Many contrasted this with their less positive experience of mental illness and mental health services. The women interviewed were active participants in their cancer treatment and did not report feeling stigmatised because of their mental health experiences. A lack of connection between cancer and mental health services was described, but this was not regarded as necessarily a bad thing. This study begins to counter the stereotypes of the difficult patient or the person unable to understand and cooperate in their own care which are prevalent in the literature. Further work is needed to understand the reasons for disparities in cancer outcomes.